1977
DOI: 10.1021/jm00211a007
|View full text |Cite
|
Sign up to set email alerts
|

11,12-Secoprostaglandins. 1. Acylhydroxyalkanoic acids and related compounds

Abstract: The synthesis is described of a series of acylhydroxyalkanoic acids which embody structural modifications of that class of secoprostaglandins which are formally derived from the natural substances by scission of the cyclopentane ring between carbon atoms 11 and 12. These analogues have been tested for their ability to stimulate cAMP formation in the mouse ovary, a characteristic action of the (E)-prostaglandins, and for their ability to bind to the rat lipocyte prostaglandin receptor. Certain members of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In the meantime, the problem of the possibility of the occurrence of prostaglandins themselves in plants remains unsolved. It should be mentioned, that the presence of a five-membered ring is not a necessity for the manifestation of affinity towards prostaglandin receptors, as was pointed out earlier in a series of papers concerning synthetic seco-prostaglandins [39][40][41][42]. It is not certain yet which of the isomers of the described trihydroxyoctadecadienoic acids possesses the greatest affinity for the receptors and displays the highest activity.…”
Section: Scheme2mentioning
confidence: 99%
“…In the meantime, the problem of the possibility of the occurrence of prostaglandins themselves in plants remains unsolved. It should be mentioned, that the presence of a five-membered ring is not a necessity for the manifestation of affinity towards prostaglandin receptors, as was pointed out earlier in a series of papers concerning synthetic seco-prostaglandins [39][40][41][42]. It is not certain yet which of the isomers of the described trihydroxyoctadecadienoic acids possesses the greatest affinity for the receptors and displays the highest activity.…”
Section: Scheme2mentioning
confidence: 99%
“…Zn(OTf) 2 was dried overnight at 120°C under vacuum prior use. Tetradeca-6,8-diene 17b and compounds (S)-6, 26 (S)-7, 27 (S)-10, 28 and were prepared according to published procedures. (-)-N-Methylephedrine and (S)-oct-1-yn-3-ol are commercially available.…”
Section: Scheme 5 Reagents and Conditionsmentioning
confidence: 99%
“…1.25-1.33 (m, 14 H, CH 2 ), 2.20 (m, 2 H, CH 2 C≡C), 4.35 (t, 1 H, J = 6.0 Hz, CHOH). 13 C NMR (CDCl 3 ): d = 14.0 (CH 3 ), 18.2 (CH 2 C≡C), 22.5,22.6,24.9,28.5,28,6,31.5,38.2,62.7 (CHOH), 85.9 (C≡C).…”
Section: Tetradec-7-yne-69-diol (8)mentioning
confidence: 99%
“…Subsequently, we showed that acids in several series3,4 isosteric with these acylhydroxyalkanoic acids display similar biological properties. The most thoroughly studied of these series is that of the sulfonamide isosteres4 of which 7-[JV-(4hydroxynonyl)methanesulfonamido]heptanoic acid (2) is an active representative.…”
mentioning
confidence: 99%